Extinction and Retrieval + Extinction of Conditioned Fear Differentially Activate Medial Prefrontal Cortex and Amygdala in Rats - Lee, Hongjoo J.; Haberman, Rebecca P.; Roquet, Rheall F.; Monfils, Marie-H. (Frontiers in Behavioral Neuroscience, 2016)
Pairing a previously neutral conditioned stimulus (CS; e.g., a tone) to an aversive unconditioned stimulus (US; e.g., a footshock) leads to associative learning such that the tone alone comes to elicit a conditioned response (e.g., freezing). We have previously shown that an extinction session that occurs within the reconsolidation window (termed retrieval+extinction) attenuates fear responding and prevents the return of fear in Pavlovian fear conditioning (Monfils et al., 2009). To date, the mechanisms that explain the different behavioral outcomes between standard extinction and retrieval+extinction remain poorly understood. Here we sought to examine the differential temporal engagement of specific neural systems by these 2 approaches using Arc catFISH (cellular compartment analysis of temporal activity using fluorescence in situ hybridization). Our results demonstrate that extinction and retrieval+extinction lead to differential patterns of expression, suggesting that they engage different networks. These findings provide insight into the neural mechanisms that allow extinction during reconsolidation to prevent the return of fear in rats.